Corporate Governance and Capital Structure Dynamics: A Case of Nepalese Commercial Banks - Bhatta, Kamala Kumari; Sharma, Gaurav; Kunwar, Kushal; Sah, Laxmi Kumari; Pokhrel, Lelina (Nepalese Journal of Business, 2025)
The study examines the effect of corporate governance on capital structure dynamics of Nepalese commercial banks. Total debt to equity ratio and total debt to asset ratio are selected as the dependent variables. The selected independent variables are board size, independent director, board meeting, female director, audit committee and institutional ownership. The study is based on secondary data of 10 commercial banks with 100 observations for the period from 2012/13 to 2021/22. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, publications and websites of Nepal Rastra Bank (NRB) and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of corporate governance on the capital structure dynamics of Nepalese commercial banks. The study showed that institutional ownership has a positive impact on total debt to equity ratio and total debt to asset ratio. It shows that increase in institutional ownership leads to increase in total debt to equity ratio and total debt to asset ratio. Similarly, female director has a negative impact on total debt to equity ratio and total debt to asset ratio. It implies that increase in female board directors in the board leads to decrease in total debt to equity ratio and total debt to asset ratio. Moreover, board meetings have positive impact on total debt to equity ratio and total debt to asset ratio. It shows that increase in number of board meetings leads to decrease in total debt to equity ratio and total debt to asset ratio. Similarly, board size has a negative impact on total debt to equity ratio and total debt to asset ratio. It means increase in board size leads to decrease in total debt to equity ratio and total debt to asset ratio. Likewise, audit committee has a positive impact on total debt to equity ratio and total debt to asset ratio. It means that increase in audit committee size leads to increase in total debt to equity ratio and total debt to asset ratio. Furthermore, independent director has a positive impact on total debt to equity ratio and total debt to asset ratio. It means that increase in independent directors leads to increase in total debt to equity ratio and total debt to asset ratio.